A class of effective decarboxylative perfluoroalkylating reagents: [(phen)2Cu](O2CRF). Issue 20 (26th April 2016) - Huang, Yangjie; Ajitha, Manjaly J.; Huang, Kuo-Wei; Zhang, Zhongxing; Weng, Zhiqiang
Abstract : A class of effective reagents [(phen)2 Cu](O2 CRF ) for the decarboxylative perfluoroalkylation of aryl and heteroaryl halides have been invented. Abstract : This article describes the invention of a class of effective reagents [(phen)2 Cu](O2 CRF ) (1 ) for the decarboxylative perfluoroalkylation of aryl and heteroaryl halides. Treatment of copper tert -butyloxide with phenanthroline ligands, with subsequent addition of perfluorocarboxylic acids afforded air-stable copper(i ) perfluorocarboxylato complexes1 . These complexes reacted with a variety of aryl and heteroaryl halides to form perfluoroalkyl(hetero)arenes in moderate to high yields. Computational studies suggested that the coordination of the second phen ligand may reduce the energy barrier for the decarboxylation of perfluorocarboxylate to facilitate perfluoroalkylation.